KARAKTER VEGETASI, KEANEKARAGAMAN MAKROZOOBENTOS DAN KARBON PADA SEDIMEN DI KAWASAN MANGROVE NUSA LEMBONGAN DAN ESTUARI PERANCAK - Janaguna, I Made Abdi; Arthana, I Wayan; Watiniasih, Ni Luh (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2023)
Natural mangroves can be found in Nusa Lembongan, which is bordered by coral reefs, while in the Perancak Estuary, some of the lands are former ponds. The aim of the study was to determine the density, canopy cover, and organic carbon content in mangrove sediments. Data were collected from 3 stations, using transects measuring 10 x 10 m to determine density, height, trunk circumference, and canopy cover, as well as macrozoobenthos sampling. The mangrove density in Lembongan is very high, the tree height reaches 8 – 10 meters, and the mangrove canopy cover is in a good category. The macrozoobenthos diversity index is in the medium category and the carbon content in the sediments is high. Mangroves in Perancak Estuary are densely dense, with an average tree height of 8 meters, and canopy cover in the good category. The index of macrozoobenthos diversity was moderate and the organic carbon in the sediments was lower than in the mangroves at Nusa Lembongan. The character of the mangrove vegetation is different in the two areas. The Nusa Lembongan mangrove growing area is directly opposite the sea, but in the Perancak Estuary, it tends to be closed and flows by a large river around it. The mangrove growth zone is still natural in the Nusa Lembongan area, in contrast to the Perancak Estuary mangrove area which has been rehabilitated at several points. Keywords: Mangrove vegetation; macrozoobenthos; carbon on sediment